FLASHCARD AS A LEARNING MEDIA TO MOTIVATE STUDENTS IN LEARNING VOCABULARY - Chusnul Chotimah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
Abstract This research is about how to motivate students in learning vocabulary by using flashcard as a learning media. The purpose of this research is to find out that flashcard can motivate students to learn vocabulary. This research was conducted on the seventh grade at Darul Hikmah Junior High School Jati Asih. The researcher found that students’ attendance level in this school cannot reach the target. This research did about six months in academic year 2020-2021. The participants are 32 students. This research used qualitative methods and using questionnaires as the instrument to the students. From the answer of questionnaires can be seen whether the flashcard can motivate students in learning vocabulary.